2016
DOI: 10.5296/jsss.v3i2.9528
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction in the Banking Industry in Ghana: A Case of GCB Bank Limited in Wa Municipality

Abstract: <p>The banking industry in the Wa Municipality has experienced some growth over the past decade. This results in increased competition among banks in the industry as each bank tries to capture a greater market share. Banks achieve competitive advantage through innovations of products that reflect customers’ expectations. Despite this competition, customer satisfaction in GCB Bank Limited is perceived to be low. However, there is no empirical evidence to establish whether the products and services deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Hence, it is concluded that the decisions for all the null hypotheses H 1 , H 2 , H 3 , and H 4 have been supported, and finally concluded that empathy, reliability, competence and online banking have significant positive impact on customer satisfaction. The results of study are in congruence with the past research findings (Rather, Sharma 2017;Adams et al 2016;Long 2016;Amin, Isa 2008;Anderson, Sullivan 1993;Arasli et al 2005;Awan et al 2011;Haron et al 1994;Levesque, McDougall 1996;Othman, Owen 2002;Raza et al 2015;Taylor, Baker 1994).…”
Section: Confirmatory Factor Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, it is concluded that the decisions for all the null hypotheses H 1 , H 2 , H 3 , and H 4 have been supported, and finally concluded that empathy, reliability, competence and online banking have significant positive impact on customer satisfaction. The results of study are in congruence with the past research findings (Rather, Sharma 2017;Adams et al 2016;Long 2016;Amin, Isa 2008;Anderson, Sullivan 1993;Arasli et al 2005;Awan et al 2011;Haron et al 1994;Levesque, McDougall 1996;Othman, Owen 2002;Raza et al 2015;Taylor, Baker 1994).…”
Section: Confirmatory Factor Analysissupporting
confidence: 89%
“…Customer trust, satisfaction and predictability of customer loyalty were found in an investigation (Phung 2016;Garbarino, Johnson 1999;Gustafsson et al 2005). In the Malaysian context, the studies concluded the positive influence of customer satisfaction on image, customers' trust, and customers' loyalty, with special reference to Islamic banking (Adams et al 2016;Amin et al 2013;Hoq et al 2010).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to achieve customer satisfaction, organizations seek to meet his or her needs in the appropriate manner. The most important way to achieve this goal is to provide customers with high quality goods and services (Adams et al, 2016). Cengiz (2010) stated that the definition of satisfaction includes three main elements: the goal that the client seeks to reach, and the process of assessing the extent to which this goal is achieved through comparison with another situation or situation using the means of evaluation and finally the evaluation result that confirms or denies the achievement of the goal.…”
Section:  Tourist Satisfaction Definitionmentioning
confidence: 99%
“…The present study was based on a questionnaire developed by reference to previous studies (Murphy et al, 2000;Parasuraman et al, 2002;Gustafsson et al, 2005;Kouthouris and Alexandris, 2005;Chen and Tsai, 2007;Esu et al, 2010;Thitthongkam and Walsh, 2011;Al-Ababneh, 2013;Ngugi, 2014;Latiff and Imm, 2015;Ramseook-Munhurrun et al, 2015;Adams et al, 2016;Jani and Nguni, 2016;Prayogo and Kusumawardhani, 2016;Tsaur et al, 2016;Mohammed and Hamdi, 2017;Pawaskar and Goel, 2017) to collect data from the study sample. The questionnaire was designed to collect data according to the five-point Likert scale, which includes the following points: "strongly agree", "agree", "neutral", "disagree", and "strongly disagree".…”
Section: Study Tool: the Questionnairementioning
confidence: 99%